Computational studies reveal mechanism by which quinone derivatives can inhibit SARS-CoV-2. Study of embelin and two therapeutic compounds of interest, methyl prednisolone and dexamethasone. Issue 12 (December 2020) - Caruso, Francesco; Rossi, Miriam; Pedersen, Jens Z.; Incerpi, Sandra
Abstract: Background: Quinones are reactive to proteins containing cysteine residues and the main protease in Covid-19 contains an active site that includes Cys145. Embelin, a quinone natural product, is known to have antiviral activity against influenza and hepatitis B. Preliminary studies by our group also indicate its ability to inhibit HSV-1 in cultured cells. Methods: Docking and DFT methods applied to the protease target. Results: a mechanism for this inhibition of the SARS-CoV-2 Mpro protease is described, specifically due to formation of a covalent bond between S(Cys145) and an embelin C(carbonyl). This is assisted by two protein amino acids (1) N(imidazole-His41) which is able to capture H[S(Cys145)] and (2) HN(His163), which donates a proton to embelin O(carbonyl) forming an OH moiety that results in inhibition of the viral protease. A similar process is also seen with the anti-inflammatory drugs methyl prednisolone and dexamethasone, used for Covid-19 patients. Methyl prednisolone and dexamethasone are methide quinones, and possess only one carbonyl moiety, instead of two for embelin. Additional consideration was given to another natural product, emodin, recently patented against Covid-19, as well as some therapeutic quinones, vitamin K, suspected to be involved in Covid-19 action, and coenzyme Q10. All show structural similarities with embelin, dexamethasone and methyl prednisolone results. Conclusions: Our data on embelin and related quinones indicate that these natural compounds may represent a feasible, strategic tool against Covid-19.